Neoplastic transformation-associated stimulation of the in vitro resolution of concatemer junction fragments from minute virus of mice DNA - Simon, Gaëlle; Rommelaere, Jean (Journal of virology, 1999)
Minute virus of mice (MVM) shows an oncotropic behavior reflected by its ability to amplify its genome more efficiently in a number of transformed versus normal cells. In vivo and in vitro studies revealed that the major effect of cell transformation on MVM DNA replication occurs at the level of double-stranded replicative-form amplification. In particular, resolution of MVM DNA concatemers into monomers was found to be highly sensitive to neoplastic transformation.
Gesehen am 11.02.2021